(untitled) (Research, Society and Development, 2023)
Introduction: Thoracic outlet syndrome (TOS) has been discerned since the 19th century as a complex of symptoms caused by compression of structures belonging to the thoracic outlet. Because it is a little known pathology and has a diverse symptomatological picture, there are currently difficulties in its diagnosis, being underreported or even undiscovered by the medical team. Objective: The objective of this study is to conduct a data survey related to the anatomoclinical aspects of Thoracic Outlet Syndrome, emphasizing the importance of understanding this condition in the medical curriculum. Methodology: This is a narrative bibliographic review, researched in PubMed database. There were 17 articles selected for the study, written in English, from 2019 to 2023, whose main theme was limited to the descriptors. Results: TOS can occur in three different regions: the scalene triangle, the costoclavicular space and the pectoral space, and these locations are capable of causing compression of the neurovascular bundle. The associated symptoms are as diverse as possible and depend on the structures affected in this scenario, such as limitation of movement, pain on movement, tingling and shocks in the upper limbs. The diagnostic process requires attention to the patient’s history and detailed physical examination, followed by imaging and confirmatory tests. In the treatment, a multidisciplinary team and extensive therapy are required due to the multifactorial clinical presentation. Conclusion: Regarding the above, the differential diagnosis is important to define the precise and definitive therapy, in order to make them more present in the medical work, given that an early diagnosis favors effective care for the affected patient.